Reporting Pandemic, Engaging Public; The Citizen Participation in LaporCovid-19 Platform During Covid-19 Outbreak in Indonesia - Ingki Rinaldi; Samiaji Bintang Nusantara; Maria Advenita Gita Elmada (Universitas Multimedia Nusantara, 2023)
Credible data and information for handling the Covid-19 pandemic in Indonesia are relatively minimal. The quality of public policies to deal with diseases classified as emerging non-natural disasters tends to be low, especially during the early stages of handling the Covid-19 pandemic. Several figures from civil society organizations, journalists, public health practitioners, and information technology experts took the initiative to develop an information reporting platform related to the pandemic that involved citizen participation in helping overcome this. The citizen platform was then developed into the practice of citizen journalism. This study describes the application of the concept of citizen reporting, which has developed into citizen journalism as an instrument for collecting data and information on Covid-19 cases in Indonesia. Especially in the case of the